Analisis Pengaruh GCG dan Kinerja Keuangan Terhadap Pengungkapan Islamic Social Reporting (ISR) - Nindya Tyas Hasanah; Novi Wulandari Widiyanti; S. Sudarno (e-Journal Ekonomi Bisnis dan Akuntansi, 2018)
This study aims to analyze of good corporate governance and financial performance influences to disclosure Islamic Social Reporting (ISR). Islamic Social Reporting (ISR) is a social responsibility disclosure index accordance to the sharia principles. Populations in this study are all companies that listed in Jakarta Islamic Index exchange in 2011-2015. The sampling method in this tudy is puposive sampling. The total number of samples in this study were 55 research samples. The disclosure of ISR is obtained by content analysis through scoring method from corporate annual reports. The analytical techniques was conducted by descriptif statistic and classical assumption test and also hypothesis was tested using multiple liniear regression method, Adjusted R2 test, F test and t test. The analysis showed that audit committee size, liquidity and profitability significantly affect the disclosure of ISR. Meanwhile, commissioners board size and leverage does not affect the disclosure of ISR. Keywords: Islamic Social Reporting (ISR), good corporate governance, financial performance, Jakarta Islamic Index